(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study investigates the ramifications of blockchain technology on the future landscape of commercial banks in the Kurdistan Region of Iraq, drawing insights from expert perspectives. The evolution of blockchain has significantly reshaped all facets of banking services and operations, resulting in a paradigm shift away from the traditional banking modus operandi in terms of systems, external events, and human intervention. Employing the Analytical Hierarchy Process (AHP) methodology and utilizing SPSS software (Version 26), the study analyzed data collected through questionnaires distributed among banks and universities in the Kurdistan Region of Iraq, totaling 90 responses. The findings reveal a notable, statistically significant inverse correlation between blockchain adoption and the future trajectory of commercial banks in the Kurdistan Region. Increased integration of blockchain technology enhances the resilience and viability of commercial banks, thereby reducing the likelihood of adverse impacts. Moreover, blockchain technology demonstrates tangible and positive prospects for the future of commercial banking, facilitating enhanced operational efficiency and cost reduction through streamlined processes and accelerated transactions, one of the key recommendations derived from the research is the necessity for banks to adopt blockchain technology. This technology contributes to reducing the costs of banking services provided in the Kurdistan region and enhances operational efficiency by minimizing intermediaries and expediting transfer and settlement processes.